MARKETING ANALYSIS OF GAHARU (AQUILARIA MALACCENSIS) AT DENDANG VILLAGE STABAT DISTRICT : (Case Study: CV. Cahaya Gaharu) - Mahendra, Didik; Siregar, Gustina; Sinaga, Hardiansyah (Journal of Agriculture, 2022)
This study aims to determine the pattern of agarwood marketing channels, and analyze the marketing efficiency of agarwood in CV. Cahaya Gaharu Village Dendang Kec. Stabat. The type of research used is descriptive and qualitative. Determination of the research location is done intentionally or purposively. The analysis technique used is to determine the pattern of marketing channels and calculate marketing margins. The marketing process carried out by CV. Cahaya Gaharu creates a marketing channel, namely CV. Cahaya Gaharu by coming to the farmer's place and buying it according to a predetermined price, then CV. Cahaya Gaharu sells it or markets it domestically or abroad. The marketing margin obtained from the only marketing channel is Rp. 6,980,000 per kilogram of wood, the share margin received is very small, namely 0.29%. This is because farmers sell directly to retailers who sell agricultural products in the country and abroad. Efficiency in the marketing channel of 40% indicates that the marketing channel is less efficient. The lack of efficiency from this business process is due to the many challenges faced, such as transportation costs and harvesting agarwood which takes a long life of up to 7 years, there is uncertainty in harvesting agarwood which can worsen supply.